The Social Construction of Market Value: Institutionalization and Learning Perspectives on Stock Market Reactions - Zajac, Edward J.; Westphal, James D. (American Sociological Review, 2004)
This study advances a social constructionist view of financial market behavior. The paper suggests that the market's reaction to particular corporate practices, such as stock repurchase plans, are not, as financial economists contend, simply a function of the inherent efficiency of such practices. Rather, stock market reactions are also influenced by the prevailing institutional logic and the degree of institutionalization of the practice. The theory first predicts that the emergence of the agency perspective on corporate governance in the mid-1980s represented a powerful new institutional logic that would lead the market to reverse its prior aggregate reaction to stock repurchase plans in the United States. The paper then considers the potential for institutional decoupling of repurchase plans and develops competing hypotheses about how the market value of these policies might have changed as more firms formally adopted, but did not implement, the plans over time. In contrast to a financial economic perspective on market valuation, which suggests that markets should discount the value of a policy as evidence of non-implementation accumulates, this study posits that institutionalization processes might increase the market value of a policy as more firms adopt it, despite growing evidence of decoupling. Implications for institutional theory and theoretical perspectives on capital markets are discussed.